Learning Curve of Robot-Assisted Thymectomy: Single Surgeon's 7-Year Experience - Meacci, Elisa; Nachira, Dania; Congedo, Maria Teresa; Petracca-Ciavarella, Leonardo; Vita, Maria Letizia; Porziella, Venanzio; Chiappetta, Marco; Lococo, Filippo; Tabacco, Diomira; Triumbari, Elizabeth Katherine Anna; Margaritora, Stefano (Frontiers in Surgery, 2022)
Background Robot-assisted thymectomy (RAT) has rapidly emerged as the preferred approach over open trans-sternal or video-assisted thoracoscopy for the surgical treatment of thymomas and non-thymomatous myasthenia gravis (MG). The aim of this study was to describe and discuss the learning curve (LC) of a single surgeon performing 113 consecutive RATs. Methods A single-center retrospective analysis of prospectively collected clinical data was performed on all patients who had been operated on by the same surgeon in an RAT setting between October 2013 and February 2020. The cumulative sum (CUSUM) analysis of the operative time was used to define the completion of the learning curve (CLC) in RAT. The CLC was separately calculated for myasthenic patients, non-myasthenic patients, and docking time. Results In myasthenic patients, the CLC cut-off was found in 19 patients. Considering the CLC cut-off of 19 patients, the mean operative time in phase 1 (first 19 cases) was 229.79 ± 93.40 min, while it was 167.35 ± 41.63 min in phase 2 (last 51 cases), p≪0.001. In non-myasthenic patients, the CLC cut-off was found in 16 cases. The mean operative time in phase 1 (first 16 cases) was 277.44 ± 90.50 min, while it was 169.63 ± 61.10 min in phase 2 (last 27 cases), p = 0.016. The LC for docking time was reached at 46 cases, recording a significant reduction of time after the first phase (28.09 ± 5.37 min vs. 19.75 ± 5.51 min, p≪0.001). The intraoperative and 30-day mortality were null in all phases of the LC in both myasthenic and non-myasthenic patients. There were no differences between the two phases of the LC in terms of blood loss, duration of postoperative drainage, and postoperative stay in both myasthenic and non-myasthenic groups. However, significantly higher hospital readmission at 30 days post surgery was recorded for myasthenic patients operated on during the first phase of the LC (2 cases vs. 0, p = 0.02). Conclusions According to our data, LC in RAT seems to be steep, and RAT confirms to be safe even before reaching CLC.